The addition of green propolis to laying hens had positive effects on egg quality: Lower bacteria counts in the shell and lipid peroxidation in the yolk - Casagrande A.C.* (2021)
© 2021, Academia Brasileira de Ciencias. All rights reserved.This study aimed to determine whether the addition of green propolis extract to the diet of laying hens would improve egg quality and bird performance and decrease bacterial contamination of eggs. Forty-fi ve brown Hy-line laying hens were used, divided into fi ve groups with three replicates each and three animals per cage: T0 - diet without propolis; T5 - 5 grams of propolis per kg of feed; T10 - 10 grams of propolis per kg of feed; T20 - 20 grams of propolis per kg of feed and T30 - 30 grams of propolis per kg of feed. The quality of fresh eggs was made on day 21 of the experiment, and eggs were stored for 21 days. Greater specifi c gravity was observed in fresh eggs in T5 birds and stored eggs for T10. TBARS in fresh eggs, we found that T30 eggs had lower levels compared to other treatments. T20 eggs had the lowest total bacterial count and the lowest total coliform count in the eggshells of T10 and T20 chickens. The count of E. coli in the peel was lower for T20 and T30 than T0 and T5. The consumption of propolis did not interfere with the hens’ egg production rate but reduced food intake and consequently reduced feed conversion. We concluded that the addition of green propolis in the diet of laying birds proved effi cient in reducing bacterial contamination in the eggshells and reducing the lipid peroxidation of fresh and stored eggs.